ANALYSIS OF THE FAMILY OF A PATIENT WITH X-LINKED ADRENOLEUKODYSTROPHY AND LITERATURE REVIEW - JIANG Jing, JIN Yang, WU Yujiao, LIU Xuewu (精准医学杂志, 2023)
Objective To analyze the mutation site in the ATP-binding cassette subfamily D member 1 gene (ABCD1) in the family of a patient with X-linked adrenoleukodystrophy (X-ALD), and to explore the diagnosis, treatment, and prognosis of X-ALD based on the patient family clinical data and related literature. Methods The clinical data and family information of a patient with X-ALD admitted to the Neurology Department of our hospital in November 2021 were retrospectively analyzed, and relevant literature worldwide was retrieved for review and discussion. Results The main symptoms of the patient were skin blacke-ning, dizziness, headache, general discomfort, fatigue, low blood pressure, loss of appetite, and poor sleep and other symptoms associated with adrenocortical insufficiency, as well as nervous system abnormalities such as lower limb palsy. His parents, brot-her, sister, son of brother, and son of sister had no related clinical manifestations. Magnetic resonance imaging of the brain and spinal cord showed no abnormalities. Genetic testing showed that the proband had a hemizygous mutation in ABCD1 (c.1628C>T), the mother had a heterozygous mutation in ABCD1, and the father had normal ABCD1. Conclusion There are many types of X-ALD with adrenocortical hypofunction or central nervous system abnormal symptoms. In this case, the patient shows the adrenomyeloneuropathy form of X-ALD. A mutation in the exon 6 of ABCD1 (c.1628C>T:p.P543L) is the cause of the disease. Magne-tic resonance imaging may not play a decisive role in the diagnostic of X-ALD.